Schwannoma of the upper lip in an adolescent: report of a rare case - Laura Boldrin Cardoso de Souza; Aline da Luz Sousa; Luís Henrique Barbizan de Moura; Milvia Maria Simões e Silva Enokihara; Samira Yarak (Sociedade Brasileira de Dermatologia (SBD), 2024)
Schwannomas are benign nerve sheath tumors derived from Schwann cells. The sites most often involved are the head and neck (25-48%), with only 1% occurring in the oral cavity. Most schwannomas occur in adult individuals between the third and fifth decades of life. Lip involvement is extremely rare during childhood and adolescence, with few reports in the literature. The prognosis is favorable and surgical excision is the treatment of choice. We report an interesting case of upper lip schwannoma in an adolescent with successful surgical treatment and no evidence of recurrence after 4 years.